The study of the blast resistance performance of underground cavern support structures under the effect of explosive ground loads - Liu, Xinxing (Frontiers in Earth Science, 2024)
The use of support structures with good explosion resistance to support and reinforce underground projects has become a focus of concern for relevant units in order to ensure the safety of underground projects in explosive ground loads. The blast resistance of underground caverns and the influence of support parameters on blast resistance have been studied when lining and pre-stressing anchors are supported individually under dynamic and static coupling. Straight-walled arched caverns are chosen for this study because of their strong blast resistance. The influence of excavation unloading on the support structure was analyzed under the condition of a burial depth of 500 m. The study investigated the blast resistance of caves supported solely by singular concrete lining support and singular pre-stressed anchor bolt support. The research findings indicate that pre-stressed anchor bolts significantly limit the deformation capacity of surrounding rock while lining is more effective in restricting the vibration response of surrounding rock. The pre-stressed anchor bolts ensure operation within the strength range throughout the entire process with no alteration in load-bearing capacity. Increasing the thickness of the lining can reduce the vibration response of the cavern. Meanwhile, enhancing the pre-stressed anchor bolts within a certain range notably restricts the deformation response of the cavern. Therefore, the pre-stressed anchor bolts should be employed as the supporting structure to bear the excavation and unloading loads of the cavern.